Growth Spillover Dynamics From Crisis to Recovery - Poirson, Helene (IMF Working Papers; Working Paper ;, 2011)
Can positive growth shocks from the faster-growing countries in Europe spill over to the slower growing countries, providing useful tailwinds to their recovery process? This study investigates the potential relevance of growth spillovers in the context of the crisis and the recovery process. Based on a VAR framework, our analysis suggests that the U.S. and Japan remain the key source of growth spillovers in this recovery, with France also playing an important role for the European crisis countries. Notwithstanding the current export-led cyclical upswing, Germany generates relatively small outward spillovers compared to other systemic countries, but likely plays a key role in transmitting and amplifying external growth shocks to the rest of Europe given its more direct exposure to foreign shocks compared to other European countries. Positive spillovers from Spain were important prior to the 2008 - 09 crisis, however Spain is generating negative spillovers in this recovery due to a depressed domestic demand. Negative spillovers from the European crisis countries appear limited, consistent with their modest size.